Empowering Renewable Energy Awareness through Promoting Sustainable Cooking Solution with Biomass Stove Demonstration towards Energy Self-sufficiency at a Rural Islamic Boarding School in North Aceh - Alchalil, Alchalil; Setiawan, Adi; Syahputra, Azhar; Safitri, Dinda (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The growing need for sustainable and affordable energy in rural Islamic boarding schools presents both a challenge and an opportunity for innovation. This community service project showed the use of woodchip-fueled biomass stoves as an alternative cooking fuel at Al-‘Urwatul Wutsqa Islamic Boarding School in Aceh Utara. It took place in Cot Seurani Village, Muara Batu Subdistrict. The scarcity and rising cost of LPG as the main cooking fuel were the main issues, limiting cooking options in the boarding school and remote communities. Onsite training and a practical demonstration of a rocket-type biomass stove using available woodchips comprised the activity. The team conducted a simple efficiency test and distributed an illustrated operational manual to support knowledge transfer. Results showed high student interest and positive response because of the stove’s affordability, environmental benefits, and ease of use. This initiative raised awareness of renewable energy options, empowered the local community with practical solutions, and encouraged reduced reliance on fossil fuels (LPG). The program also laid the foundation for future development of energy self-sufficiency in the boarding school atmosphere.